KEMAMPUAN PREDIKSI LABA BERSIH, ARUS KAS OPERASI DAN ASET TETAP UNTUK ARUS KAS OPERASI DI MASA MENDATANG THE ABILITY TO PREDICT NET PROFIT, OPERATIONAL CASH FLOWS AND FIXED ASSETS FOR FUTURE OPERATIONAL CASH FLOWS - Dimas Ridlo Hanantika (Jurnal Ilmiah Mahasiswa FEB, 2018)
This research aims to test the ability of earnings, operational cash flows and fixed assets in predicting future operational cash flows. The data used in this research were taken from 28 manufacturing companies financial statements during 2012 until 2017 which registered in Indonesia Stock Exchange.The technique used in this research to analyze the data was the multiple regression analysis technique in SPSS 24.00 as well as to do the statistical test. Furthermore, the hypothesis testing was done by using partial significance test ( t test ) with a = 5%. The results of this research show that net profit, operational cash flows and fixed assets are able to predict the future operational cash flows and also the implication of this research is to provide information for investor in investment decision making.Key words: Net Profit, Operating Cash Flows, Fixed Assets, Manufacturing Companies